Interrelationship of Culture and Civilization: A Universal Perspective on Human Progress and Decline - Anjum, Dr. Samina; kanwal, Najeeba (Al-Amīr Research Journal for Islamic Studies, 2024)
The concepts of "culture" and "civilization" are central to the study of sociology, history, and philosophy. Culture encompasses the core values, beliefs, and principles that define humanity’s shared identity, shaping a nation’s distinctiveness within society. It plays a critical role in influencing political, social, and international institutions, giving rise to the arts, sciences, and architectural achievements. Civilization, in turn, develops through social institutions and political systems built upon cultural foundations. These can be categorized into Mentifacts (beliefs), Artifacts (material goods), and Sociofacts (social organization). Universally, civilizations that adhere to moral principles and prioritize public welfare endure and ensure humanity’s progress. Despite material advancements, humanity has suffered a spiritual and moral decline, underscoring the absence of a constructive culture. A superior civilization transcends national and regional boundaries, offering a universal code of conduct and fostering human progress across all fields. Keywords: Culture, Civilization, Universal Values, Moral Decline, Human Progress, Public Welfare, Sociological Impact, Spirituality.